Assessment of Groundwater Wells Pollution by Some Heavy Metals in El-Beida City-Libya - Galal M. Elmanfe; Tariq A. Tyeb; Kareima A.Abdelghani; Adel A. Abdulathim; Jibreel A. Asbeeh; Huda S. Muftah; Ameerah F. Ali (Journal of Pure & Applied Sciences, 2022)
One of the most important concerns is the presence of heavy metals in water. Heavy metal pollution in groundwater is a major concern, because of their toxicity and hazard to human life and the environment. The aim of this study was to determine the quantity of five heavy metals present in groundwater wells in different sites of El-Beida city. Groundwater wells samples were collected in January 2022 from 10 randomly selected wells throughout the region and analyzed in order to determine the content of a number of heavy metals namely: Lead, Copper, Iron, Manganese, and Nickel using an Atomic Absorption Spectrophotometer (AAS), and their levels were compared to the maximum contamination limits specified by the World Health Organization (WHO) and the Libyan National Centre for Standardization and Metrology (LNCSM). The results in the current study indicate there is variation among wells. The Lead (Pb) concentrations ranged between (0.33-0.50 mg/l), whereas the Copper (Cu) value ranged (0.07-0.12 mg/l), the Iron (Fe) value ranged (1.15-1.35 mg/l), the Manganese (Mn) value ranged (0.17-0.75 mg/l), and the Nickel (Ni) value ranged (0.19-0.52 mg/l). Most of the heavy metal analyzed in this study were exceed permissible limits for international standards of drinking water by WHO or LNCSM  while Copper (Cu) did not exceed permissible limits for international standards of drinking water.